Equilibrium sorption of ethylene in polyethylene: Experimental study and PC-SAFT simulations. (24th February 2015) - Chmelař, J.; Smolná, K.; Haškovcová, K.; Podivinská, M.; Maršálek, J.; Kosek, J.
Abstract: Ethylene sorption in polyethylene (PE) influences the reaction rate in polymerization reactors and the subsequent degassing of residual monomer. The knowledge of ethylene solubilities is therefore important for process design and optimization. We used a gravimetric apparatus based on a magnetic suspension balance to measure ethylene solubilities in 13 PE samples at temperatures from 60 to 150 °C. The samples were nascent reactor powders with densities from 902 to 967 kg m −3 and weight average molecular weights from 98 to 253 kg mol −1 . The experimental data were compared with the literature and the entire data set was correlated using the PC-SAFT equation of state. To evaluate the solubilities, we used swelling corrections based on experimental data and considered temperature dependent crystallinities. As a result, the ethylene solubilities decreased with increasing temperature and increasing PE crystallinity. Furthermore, we observed a temperature independent PC-SAFT binary interaction parameter k PE, ethylene . These phenomena are expected from theory, but only rarely observed for complex samples such as semi-crystalline polymers. We also propose correlations for k PE, ethylene, which enable to predict ethylene solubilities in semi-crystalline PE from the crystallinity at the experimental temperature. Graphical abstract: Highlights: Sorption of ethylene in a broad range of PE samples measured gravimetrically. Temperatures and pressures relevant to gas-phase and slurry polymerization. Solubilities evaluated considering swelling and temp. dependent crystallinity. Data correlated by the PC-SAFT equation of state. Results support the concept of elastic constraints.